THE INFLUENCE OF K-POP CULTURE IN THE FORMATION OF PHUBBING BEHAVIOR AND CONFORMITY OF PHASE C PRIMARY AGE STUDENTS AT MUHAMMADIYAH 4 PRIMARY SCHOOL SURABAYA - Abduh, Mujahied Faried; Mu’ammar, Muhammad Arfan; Arifin, Zainal (UNIVERSITAS PAKUAN, 2025)
The globalization process has had a significant impact in the spread of popular culture, especially K-Pop culture which influences the behavior of the millennial generation, including primary age students in phase C at SD Muhammadiyah 4 Surabaya. This research aims to investigate the influence of K-Pop culture on students' phubbing behavior and conformity. Through a qualitative approach with case studies, data was obtained from 80 respondents using snowball sampling techniques and questionnaires. The research results show a correlation between exposure to K-Pop culture and phubbing behavior, interpersonal conflict, and self-isolation. Additionally, there is a significant pattern of conformity to K-Pop culture, especially in terms of belief in group righteousness and the desire to be liked by the group. These findings highlight the importance of being aware of the impact of popular culture such as K-Pop on the behavior and social norms of the younger generation, as well as the need for a holistic approach in managing cultural influences in education. Thus, this research contributes to understanding the dynamics of interaction between popular culture and the behavior of the millennial generation.